Sticky information Phillips curves: European evidence - Jörg Döpke; Jonas Dovern; Ulrich Fritsche; Jiri Slacalek (European Central Bank (ECB), 2008)
We estimate the sticky information Phillips curve model of Mankiw and Reis (2002) using survey expectations of professional forecasters from four major European economies. Our estimates imply that inflation expectations in France, Germany and the United Kingdom are updated about once a year, in Italy about once each six months.
Keywords: E62; H20; H50; H62; 330; inflation expectations; Inflation persistence; Phillips curve; sticky information; Phillips-Kurve; Inflationserwartung; Schätzung; Informationsverbreitung; Frankreich; Deutschland; Großbritannien; Italien